Application research of microwave non-destructive testing technology in detecting reinforcement corrosion in concrete - Gao Zitong; Nanayakkara Ominda (MATEC Web of Conferences)
This paper presents a comprehensive elaboration on a two-port microwave non-destructive testing approach utilizing a Vector Network Analyser (VNA). The main objective of this methodology is to accurately identify the presence of reinforcing bars within the concrete and determine their degree of corrosion. This technology is based on the propagation characteristics of microwaves in both non-metallic substances and metals. Through precise measurement of key parameters such as the reflection coefficient and transmission coefficient, the existence and corrosion state of reinforcing bars can be precisely determined. Generally, the relative permittivity of ordinary Portland cement (OPC) concrete typically falls within the range of 4 to 12. The relative permittivity of corroded reinforced concrete is higher than both concrete and concrete reinforcement. The relative permittivity of corrosion depositsis relatively higher than that of reinforced concrete, enabling it to better absorb microwave energy under microwave action. This property can be utilized to distinguish the location of steel bars in existing buildings and the extent of corrosion.